Optimization of primary freeze drying conditions for powdered chicken meat hydrolysate from mechanically deboned chicken residues. Issue 10 (1st July 2020) - Söbeli, Ceyda; Kayaardı, Semra
Abstract: In this study, mechanically deboned chicken meat residues were hydrolyzed by protease enzyme and chicken meat hydrolyzate was freeze-dried in order to produce high-quality meat powder. Due to its high cost, energy and time consumption, freeze-drying conditions needed to be optimized. Response surface methodology was used for optimization with the independent variables shelf temperature, lyophilization temperature and freezing rate. The responses were sublimation time, solubility and in vitro protein digestibility. The optimum conditions were shelf temperature, 15 °C; lyophilization temperature, –10 °C; and freezing rate, 2.0 °C/min. Sublimation time, solubility and in vitro protein digestibility for this optimum conditions were found to be 590.344 min, 25.626% and 23.808%, respectively.